Queer love, Abrahamic morality, and (the limits of) American Muslim marriage - Hammer, Juliane (Theology & sexuality, 2021)
This article explores recent Muslim debates on sexuality through an analysis of American Muslim conversations on LGBTQI+ inclusion and sexual norms as they took place in the ‘Muslim American public square,’ defined as a porous space of debate, analysis, and affect that is marked by intense public scrutiny and hostility towards Muslims. It analyzes religious arguments regarding queer Muslims and contextualizes them as a specific set of patriarchal Muslim responses to the Supreme Court decision legalizing same-sex marriage in 2015 and to the attack on the Pulse Club in Orlando in 2016, exhibiting an affective investment in a stable Islamic tradition that constructs patriarchal sexual norms as the linchpin of the tradition. Muslim American debates refract broader American conversations while also being marked by distinct positionalities, arguments, and affects that preclude the possibility of categorizing the diversity of Muslim attitudes towards same-sex love and marriage either affirmatively or negatively.